Correction: Singano et al. One Health Lens on Rabies: Human–Bat Interactions and Genomic Insights of Rabies Virus in Rural Lilongwe, Malawi. Trop. Med. Infect. Dis. 2025, 10, 95 - Nathan Singano; Henson Kainga; Elisha Chatanga; Joseph Nkhoma; Gilson Njunga; Julius Chulu; Rabecca Tembo; Hirofumi Sawa; Walter Muleya (Tropical Medicine and Infectious Disease)
There was an error in the original publication [...]